PEMANTAUAN PENERAPAN KAWASAN TANPA ROKOK (KTR) DI SEKOLAH WILAYAH UPTD PUSKESMAS TAKALALA KAB. SOPPENG - Rusnah Rusnah; Andi Risva Elya Pramita (-, 2022)
ABSTRACT Non Smoking Area Application (KTR) is a solution for breathing fresh air without cigarette smoke. School is one without smoking, because smoking will disrupt teaching and learning activities. The application of smoke-free areas in schools is very important to create a clean and healthy school environment without smoke. The method used in this research is quantitative with a descriptive survey research design. The population in this study were all schools in the Takalala Community Health Center with a total of 27 schools. The sample used was a total sampling of 27 schools where the sampling technique was the same as the population. The results of the research conducted at the school in the Takalala Public Health Center area were the results of observations of the application of KTR in schools as many as 13 schools that were KTR while those that were not KTR were 14 schools. The implementation of KTR at the school level, both primary school, first high school and upper secondary school must meet 10 KTR indicators, namely there are School Decrees / Regulations related to the implementation of KTR in the school environment, there are KTR supervisor officers, no smoking is found, there is no smell of cigarette smoke, no butts are found cigarettes, no ashtrays or matches were found, there were penalties for violating KTR, no cigarette advertisements or promotions were found, there were no stalls or people selling cigarettes. It is hoped that schools that have not implemented KTR should immediately implement KTR in the school environment by taking into account the 10 indicators of KTR that have been determined, especially in making a smoking ban policy in the form of a KTR Decree and giving strict sanctions for school members who violate the smoking ban. Keywords: KTR indicators, KTR implementation, schools ABSTRAK KTR merupakan salah satu solusi menghirup udara segar tanpa asap rokok. Sekolah merupakan salah satu tanpa rokok, karena merokok akan mengakibatkan terganggunya kegiatan belajar mengajar. Penerapan kawasan tanpa rokok di sekolah sangat penting untuk menciptakan lingkungan sekolah yang bersih dan sehat tanpa asap rokok. Metode yang digunakan dalam penelitian ini adalah kuantitatif dengan desain penelitian survei deskriptif. Populasi dalam penelitian ini adalah seluruh sekolah wilayah Puskesmas Takalala dengan jumlah 27 sekolah. Sampel yang digunakan adalah total sampling sebanyak 27 sekolah dimana teknik pengambilan sampel sama dengan jumlah populasi . Hasil penelitian yang dilakukan di sekolah wilayah Puksesmas Takalala yaitu hasil observasi penerapan KTR di sekolah sebanyak 13 sekolah yang KTR sedangkan yang tidak KTR sebanyak14 sekolah. Implementasi KTR pada jenjang sekolah baik SD, SMP maupun SMA harus memenuhi 10 indikator KTR yaitu terdapat Surat Keputusan/Peraturan Sekolah terkait pelaksanaan KTR di lingkungan sekolah, ada petugas pengawas KTR, tidak ditemukan orang yang merokok, tidak tercium bau asap rokok, tidak ditemukan puntung rokok, tidak ditemukan asbak atau korek api, ada sanksi bagi yang melanggar KTR, tidak ditemukan iklan atau promosi rokok, tidak ada warung atau orang yang menjual rokok. Diharapkan kepada pihak sekolah yang belum menerapkan KTR agar segera menerapkan KTR di lingkungan sekolah dengan memperhatikan 10 indikator KTR yang telah ditentukan terutama dalam membuat kebijakan larangan merokok dalam bentuk Surat Keputusan KTR dan pemberian sanksi secara tegas bagi warga sekolah yang melanggar larangan merokok. Kata kunci: indikator KTR, penerapan KTR, sekolah